POLITICAL SUB SYSTEM OF ISLAMIC COMMUNITY WITHIN THE RUSSIAN POLITICAL SYSTEM: TOWARD THE PROBLEM OF POLITICAL COMPATIBILITY AND NON-COFLICT - D. G. Mirzakhanov (Современная наука и инновации)
The article studies the institutional characteristics of Russian Islamic sub-system in context of congruence to political system of modern Russia. The author describes the content and levels of mutual relations between Russian authorities and Islamic community. This reconfirms that on some issues of post-Soviet Russian state-building the leaders of Islamic umma has own ideas